Răspuns :
a^2 + a +6 = 0
a1,2 = (-1+/- rad(1-24)) : 2 = -1/2 +/- (i/2 * rad23) ∈ C-R.
i=rad(-1).
a1,2 = (-1+/- rad(1-24)) : 2 = -1/2 +/- (i/2 * rad23) ∈ C-R.
i=rad(-1).
[tex]A \times A + A = - 6[/tex]
[tex] {A}^{2} + A = - 6[/tex]
[tex]{A}^{2} + A + 6 = 0[/tex]
[tex]a = 1[/tex]
[tex]b = 1[/tex]
[tex]c = 6[/tex]
[tex]\Delta = {b}^{2} - 4ac[/tex]
[tex]\Delta = {1}^{2} - 4 \times 1 \times 6[/tex]
[tex]\Delta = 1 - 24[/tex]
[tex]\Delta = - 23 < 0 = > ecuatia \: nu \: are \: radacini \: reale[/tex]
[tex] = > ecuatia \: are \: radacini \: complexe[/tex]
[tex]A_{1,2} = \frac{ - b\pm \: i \sqrt{ \Delta} }{2a} = \frac{ - 1\pm \: i \sqrt{ - 23} }{2 \times 1} = \frac{ - 1\pm i\:\sqrt{ ( - 23) }}{2} [/tex]
[tex]A_{1} = \frac{ - 1 +\:i \sqrt{-23} }{2} [/tex]
[tex]A_{2} = \frac{ - 1 -\:i \sqrt{-23} }{2} [/tex]
[tex] {A}^{2} + A = - 6[/tex]
[tex]{A}^{2} + A + 6 = 0[/tex]
[tex]a = 1[/tex]
[tex]b = 1[/tex]
[tex]c = 6[/tex]
[tex]\Delta = {b}^{2} - 4ac[/tex]
[tex]\Delta = {1}^{2} - 4 \times 1 \times 6[/tex]
[tex]\Delta = 1 - 24[/tex]
[tex]\Delta = - 23 < 0 = > ecuatia \: nu \: are \: radacini \: reale[/tex]
[tex] = > ecuatia \: are \: radacini \: complexe[/tex]
[tex]A_{1,2} = \frac{ - b\pm \: i \sqrt{ \Delta} }{2a} = \frac{ - 1\pm \: i \sqrt{ - 23} }{2 \times 1} = \frac{ - 1\pm i\:\sqrt{ ( - 23) }}{2} [/tex]
[tex]A_{1} = \frac{ - 1 +\:i \sqrt{-23} }{2} [/tex]
[tex]A_{2} = \frac{ - 1 -\:i \sqrt{-23} }{2} [/tex]